2015
DOI: 10.1017/s0007114514004437
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofn-3 PUFA supplementation at different EPA:DHA ratios on the spontaneously hypertensive obese rat model of the metabolic syndrome

Abstract: The increasing incidence of the metabolic syndrome (MetS), a combination of risk factors before the onset of CVD and type 2 diabetes, encourages studies on the role of functional food components such as long-chain n-3 PUFA as preventive agents. In the present study, we explore the effect of EPA and DHA supplementation in different proportions on spontaneously hypertensive obese (SHROB) rats, a model for the MetS in a prediabetic state with mild oxidative stress. SHROB rats were randomised into four groups (n 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 45 publications
5
42
1
3
Order By: Relevance
“…In our study, the lowest serum TC and LDL-C concentrations were observed in the DHA/EPA 2:1 group and the highest serum HDL-C concentration was observed in the DHA/EPA 1:1 group, which appeared to differ from the existing report that using more or equal amounts of EPA is better than using an excess of DHA for the control of dyslipidemia in metabolic syndromes [19]. Our findings implied that a higher DHA/EPA ratio is better for reducing serum "bad cholesterol" levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, the lowest serum TC and LDL-C concentrations were observed in the DHA/EPA 2:1 group and the highest serum HDL-C concentration was observed in the DHA/EPA 1:1 group, which appeared to differ from the existing report that using more or equal amounts of EPA is better than using an excess of DHA for the control of dyslipidemia in metabolic syndromes [19]. Our findings implied that a higher DHA/EPA ratio is better for reducing serum "bad cholesterol" levels.…”
Section: Discussioncontrasting
confidence: 99%
“…However, another report demonstrated that the levels of plasma CRP were significantly decreased by EPA/DHA supplementation at 1:1 and 2:1 ratios, but not at 1:2 ratio [19]. In this study, there was no significant difference in the levels of pro-and/or anti-inflammatory factors in serum and aortic tissues between the DHA/EPA groups, which again highlights the importance of the n6/n3 PUFA ratio.…”
Section: Accepted Manuscriptsupporting
confidence: 42%
See 2 more Smart Citations
“…As the decades passed, n-3 PUFAs have been developed as dietary supplements, and it is now widely accepted that n-3PUFAs are incorporated as structural components into cell membrane phospholipids in the blood and tissues, and they mediate an array of biological effects [2,3].…”
mentioning
confidence: 99%